Analysis Of The Effect Of Knowledge And Work Design On Employee Performance With Job Satisfaction As An Intervening Variable In The Eastern Crossroad Preservation Project In Riau Province - Railiza Saragih; Sri Rahayu; Muhammad Alfahmi (International Journal of Management, Economic and Accounting, 2025)
Research methods applied in study This is study quantitative . for test and prove hypothesis that has been made through various test and data processing . Data collection methods sample in research This is in a way census so that all population in research This will become sample study that is all employee active in PT Adhi Karya (Persero) Tbk on the Project Preservation of the East Cross Road in Riau Province , totaling 103 people . Based on results study can seen that in a way partial T- statistic value and P- value For variable knowledge to performance each employee is T- statistic 3.688 ≥ 1.660 and P- value 0.000 ≤ 0.05 , so that can concluded knowledge own significant influence to performance employees . Then , the T- statistic value and P- value For variable design Work to performance each employee is T- statistic value 0.056 ≤ 1.660 and P- value 0.955 ≥ 0.05, so can concluded design Work No own significant influence to performance employees . Then , the T- statistic value and P- value For variable satisfaction Work to performance each employee has a T- statistic of 3.365 ≥ 1.660 and a P- value of 0.001 ≤ 0.05, so that can concluded satisfaction Work own significant influence to performance employees . Then , the T- statistic value and P- value For variable knowledge to satisfaction work respectively amounted to T- statistic 0.504 ≤ 1.660 and P- value 0.615 ≥ 0.05, so that can concluded knowledge No own significant influence to satisfaction work . Then , the T- statistic value and P- value For variable design Work to satisfaction each work is T- statistic 3.240 ≥ 1.660 and P- value 0.001 ≤ 0.05, so that can concluded design Work own significant influence to satisfaction work . Then , the T- statistic value and P- value For variable knowledge to performance employee through satisfaction each work is T- statistic 0.460 ≤ 1.660 and P- value 0.646 ≥ 0.05, so that can concluded knowledge No own significant influence to performance employee through satisfaction work . Then , the T- statistic value and P- value For variable design Work to performance employee through satisfaction each work is T- statistic 2.906 ≥ 1.660 and P- value 0.004 ≤ 0.05, so that can concluded design Work own significant influence to performance employee through satisfaction Work .